HIV-1 Tat and cocaine mediated synaptopathy in cortical and midbrain neurons is prevented by the isoflavone Equol - Bertrand, Sarah; Hu, Calvin; Aksenova, Marina; Mactutus, Charles; Booze, Rosemarie (Frontiers in Microbiology, 2015)
Illicit drugs, such as cocaine, are known to increase the likelihood and severity of HIV-1 associated neurocognitive disorders (HAND). In the current studies synaptic integrity was assessed following exposure to low concentrations of the HIV-1 viral protein Tat 1-86B, with or without cocaine, by quantifying filamentous actin (F-actin) rich structures (i.e., puncta and dendritic spines) on neuronal dendrites in vitro. In addition, the synapse-protective effects of either R-Equol (RE) or S-Equol (SE; derivatives of the soy isoflavone, daidzein) were determined. Individually, neither low concentrations of HIV-1 Tat (10 nM) nor low concentrations of cocaine (1.6 μM) had any significant effect on F-actin puncta number; however, the same low concentrations of HIV-1 Tat + cocaine in combination significantly reduced dendritic synapses. This synaptic reduction was prevented by pre-treatment with either RE or SE, in an estrogen receptor beta dependent manner. In sum, targeted therapeutic intervention with SE may prevent HIV-1 + drug abuse synaptopathy, and thereby potentially influence the development of HAND.